Theory and Practice: Reflections on Convergence in United Kingdom Universities - Field, Clive D. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
This paper reviews the extent and nature of convergence of information services in the United Kingdom higher education sector. It traces the history of the process of convergence since the 1980s; considers the principal drivers behind it; outlines some of the implementation issues which have arisen; and evaluates its impact. Although drawing upon a fairly substantial published literature, and the author’s personal knowledge of convergence in a number of institutions, extensive use is made, especially in the second half of the essay, of the experience of convergence at the University of Birmingham (through Information Services) since 1995. In this way, the paper updates and extends the description and analysis of Birmingham developments previously reported in Field (1996, 1999) and Pugh (1997a: 50-62). While the Birmingham model of convergence is certainly not being held up as a blueprint for other services to follow, it is of some wider interest for two reasons: in being the first major example of convergence in a very large, diverse, traditional and researchintensive British university (with an annual turnover of £250 million and 35,000 registered library users); and in adopting a fairly radical approach to management structure, one in which „existing departmental barriers have been completely removed and a quite new structure developed” (Law, 1998: 55).